Gambaran Pengetahuan, Sikap dan Dukungan Suami Tentang Imunisasi TT pada Ibu Hamil di Puskesmas Sikumana - Odilia D. Odang; Amelya B. Sir; Indriati A. Tedju Hinga (Yayasan Literasi Sains Indonesia, 2023)
Neonatorum tetanus disease is the second cause of death throughout the world in diseases that can be prevented through vaccination. Based on the Kupang City Health Report, the Sikumana Health Center Working Area has a low toxoid tetanus immunization coverage. This study aims to determine the description of the knowledge, attitudes and support of husbands about immunization tetanus toxoid in pregnant women at the Sikumana Health Center. This type of research is descriptive quantitative and done by the survey method. The sample in this study were 60 pregnant women who were selected using the Accidental Sampling technique. Data collection uses KIA book questionnaires and observations. The data analysis used is an univariate analysis that only looks at the picture of the frequency distribution of each variable studied. The results showed that the immunization status of trimester III pregnant women was incomplete as many as 91.7%. Knowledge of pregnant women in trimester III is categorized as little as 76.7%. The attitude ofÂ trimester III pregnant women is categorized as much as 85% and husband's support categorized as not supporting as many as 83.3%. It is expected that the Sikumana Health Center can increase counseling on tetanus toxoid immunization not only at the meeting of mother in Posyandu, but also for women of childbearing age and the wider community to know the importance of tetanus toxoid immunization.